A systematic literature review on factors of socio-environmental vulnerability associated with water-borne diseases - Mazuze, Helia; Almendra, Ricardo; Santana, Paula (The Journal of Infection in Developing Countries, 2023)
Introduction: Diarrhoeas, acute gastroenteritis with moderate dehydration, malaria and cholera are water-borne diseases with a high incidence in childhood and are one of the principal causes of morbidity and mortality in children under the age of 5 years, and predominantly so in developing countries. Various factors influence the population’s vulnerability to these diseases. The objective of this work was to identify the factors of socio-environmental vulnerability associated with the occurrence of water-borne diseases (diarrhoeas, acute gastroenteritis with moderate dehydration, malaria and cholera). Methodology: A systematic review of the literature was performed, with the databases PubMed, Scopus, B-On and Scielo to identify studies published between 2010 and 2021. Results and Conclusions: The results showed that the most significant factors related to vulnerability to water-borne diseases have to do with sanitation and the availability of clean drinking water; however, temperature and precipitation were also found to exert considerable influence, together with the demographic factor.